Gambaran Kualitas Hidup Pada Pasien Ca Mamae Yang Menjalani Kemoterapi Di Rsup Dr. M. Djamil Padang - Rifka Putri Andayani; Rizka Ausrianti (STIKes MERCUBAKTIJAYA, 2023)
Cancer is a disease characterized by the presence of changes in normal cells into abnormal cells that are not controlled and can metastasize, both invading nearby tissues and distant biological tissues. According to estimates from the World Health Organization (WHO) in 2019, cancer was the first or second cause of death before the age of 70 in 112 out of 183 countries. This study aims to determine the picture of quality of life in ca mamae sufferers undergoing chemotherapy at RSUP dr. M.djamil padang. This type of research uses a descriptive approach. The sample was 60 respondents with a non-random sampling technique with accidental sampling technique. The measuring instrument used is in the form of a HARS (Hamilton Anxiety Rating Scale) questionnaire consisting of 14 pernyatann. The results of the study found that most of the breast cancer patients, namely as many as 78.3% who underwent chemotherapy in the chemotherapy room of RSUP M.Djamil, Padang City, had a poor quality of life. The conclusion of this study is that most of the quality of life of ca mamae patients undergoing chemotherapy is of poor quality. Advice for families to provide attention and support to people with ca mamae so that they can live a quality life because it can have an impact on the quality of health.